SD-Groups and Embeddings - Mikaelian, Vahagn (Armenian Journal of Mathematics, 2008)
We show that every countable SD-group G can be subnormally embedded into a two-generator SD-group H. This embedding can have additional properties: if the group G is fully ordered then the group H can be chosen to also be fully ordered. For any non-trivial word set V this embedding can be constructed so that the image of G under the embedding lies in the verbal subgroup V (H) of H.